Study into the gender-specific transition and challenges faced by female elite athletes - Tekavc, J.; Wylleman, P.; Cecic-Erpic, S.; Reints, A.; Rosier, N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Although researchers have examined how talented and elite athletes develop through (as well as after) their athletic career (Wylleman & Reints, 2010), and despite the increased participation of women in elite sport, most empirical data on the athletic career development is related to male talented and elite athletes. Methods: Taking into account the multi-level factors of influence on career development, the developmental lifespan model (Wylleman & Reints, 2010) was used as conceptual framework to conduct a preliminary study into the empirical data available on the development of female talented and elite athletes. Results: Research shows that differences in biological determinants (e.g., pregnancy) may explain the existence of female-specific career transitions and why women may show a different career path than men. At athletic level, female athletes typically specialize, achieve their peak, and end their athletic careers one to two years earlier than male athletes in the same sports. At academic/vocational level, female athletes have been found to more often continue their studies into higher education than male athletes, to benefit less from having a university degree than male athletes and also get less often jobs in the sport system, like coach or manager. Discussion: While recognizing gender differences in athletes` career development, no attempt has been made to develop gender-specific athlete career transition models. More research on the role of gender on multi-level challenges (e.g., transition into higher education, sponsorship, lifestyle) faced by female athletes is therefore warranted. This research should not only add to the development of athletic career transition models specific to elite female athletes, but extend and detail the knowledge base currently available on the gender-specific transitions faced by elite female athletes.